1991
DOI: 10.1203/00006450-199110000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hypercapnia on Maternal and Fetal Vasopressin and Catecholamine Release

Abstract: ABSTRACT. Although fetal asphyxia, i.e. hypoxemia, acidosis, and hypercapnia, increases plasma arginine vasopressin (AVP) >40-fold, hypoxemia and metabolic acidosis occurring independently cause only 5-fold and 2-fold increases, respectively. To determine the effects of hypercapnia on AVP release, we examined the effects of acute hypercapnia on AVP secretion in six pregnant sheep and their fetuses a t 135 f 4 d (x f SD), exposing the ewe successively to room air, 30% 02, 30% O 2 plus 10% C 0 2 , 30% 02, and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In these studies, fetal hypercapnia was induced through the ewe. It was reported that amniotic fluid pressure in creased during hypercapnia [5] and maternal cortisol crossed the placental barrier [8,9], With our extrauterine fetal incubation system, it was possible to observe fetal physiological change without maternal influence.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In these studies, fetal hypercapnia was induced through the ewe. It was reported that amniotic fluid pressure in creased during hypercapnia [5] and maternal cortisol crossed the placental barrier [8,9], With our extrauterine fetal incubation system, it was possible to observe fetal physiological change without maternal influence.…”
Section: Discussionmentioning
confidence: 94%
“…But very few studies have reported on changes of fetal physiological parameters such as heart rate and blood pressure during hypercapnia [4][5][6]8]. Therefore, responses of the fetal peripheral chemoreccptor to changes in PaCCE have not yet been quantified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations